2019
DOI: 10.16984/saufenbilder.490668
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Statistical Investigation of Surface Roughness in Turning of AISI 4140 Steel

Abstract: In this study, 48 HRC hardness AISI 4140 is turned on in different cutting parameters and cooling environment. The Taguchi L9 test design was developed based on the three-level cutting speed (V), feed rate (f), depth of cut (a) and cooling environment parameters. According to the L9 experimental design, the mean surface roughness (Ra) values were measured. Chip form occurring during turning is photographed. The S/N (Signal/Noise) ratios of the Taguchi experiment design in the Minitab program have been determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
3
0
3
Order By: Relevance
“…Son yıllarda, çeşitli malzemelerin tornalanması sonucu meydana gelen yüzey pürüzlülüğü ve titreşim üzerinde kesme parametrelerinin etkilerini belirlemek için deney tasarım metotlarına ve analizlerine dayanan çeşitli istatistiksel ve deneysel çalışmalar yapılmıştır [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Fakat ayna ve punta basıncının titreşim ve yüzey pürüzlülüğü üzerindeki etkisini belirlemek için optimizasyon yapan her hangi bir deneysel ve istatiksel çalışma yapılmamıştır.…”
Section: Igi̇ri̇şunclassified
See 1 more Smart Citation
“…Son yıllarda, çeşitli malzemelerin tornalanması sonucu meydana gelen yüzey pürüzlülüğü ve titreşim üzerinde kesme parametrelerinin etkilerini belirlemek için deney tasarım metotlarına ve analizlerine dayanan çeşitli istatistiksel ve deneysel çalışmalar yapılmıştır [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Fakat ayna ve punta basıncının titreşim ve yüzey pürüzlülüğü üzerindeki etkisini belirlemek için optimizasyon yapan her hangi bir deneysel ve istatiksel çalışma yapılmamıştır.…”
Section: Igi̇ri̇şunclassified
“…Yazar, yüzey pürüzlülüğü üzerinde en etkili parametrenin kesme derinliği olduğunu tespit etmiştir. ANOVA'da sırasıyla kesme derinliğinin, kesme hızının, ilerlemenin ve soğutma sıvısının Ra değerine % 95 güvenirliğinde etkilediğini tespit etmiştir [13]. Yılmaz ve ark.…”
Section: Igi̇ri̇şunclassified
“…Additionally, the surface roughness deteriorated owing to increased tool wear. Akkuş 13 investigated the effects of cutting speed, feed, depth of cut, and cooling on the turning of AISI 4140 materials. The research revealed that better surface quality was achieved at low feeds and that the chips were long and thin.…”
Section: Introductionmentioning
confidence: 99%
“…(S/N) oranlarını hesaplar ve bu değerlere göre analiz yapmamızı sağlar. Aşağıda yaygın olarak kullanılan üç S/N hesaplama yöntemi verilmiştir(Akkuş, 2019; Erkan ve ark., 2020). Deneyler için seçilen kesme parametreleri/seviyeleri, yüzey pürüzlülük ve makro sertlik ölçüm kriterleri…”
unclassified